Influence of Adhesive Wear and Thermal Degradation on the Frictional Characteristics of Paper-Based Friction Materials: A Comparative Study. (10th January 2012) - Ompusunggu, Agusmian Partogi; Sas, Paul; Van Brussel, Hendrik
Abstract : This paper discusses the effects of adhesive wear and thermal degradation on the dry frictional characteristics of paper-based friction materials against steel material. Some commercial paper-based friction materials typically used for clutch applications were subjected to adhesive wear and thermal degradation and the dry frictional characteristics were then measured at different states on a rotational tribometer. The experimental results reveal that both adhesive wear and thermal degradation have opposite effects on the frictional characteristics, where the static and kinetic coefficients of friction increase due to adhesive wear but decrease due to thermal degradation.